Production of Bioethanol and Crude Cellulase Enyzme Extract from Napier Grass (Pennisetum purpureum S.) through Simultaneous Saccharification and Fermentation - Taufikurahman Taufikurahman; Sherly - Xie (3BIO: Journal of Biological Science, Technology and Management, 2020)
Napier grass (Pennisetum purpureum S.) has been recognized for its high amounts of cellulose and hemicellulose which can be utilized for bioethanol production. Bioconversion of Napier grass to bioethanol can be performed by filamentous fungi. A fungi, Neurospora sitophila, can synthesize and secrete hydrolytic enzymes to breakdown the cellulose and hemicellulose into various monomeric sugars and simultaneously convert it to bioethanol. This study investigated the effect of Napier grass substrate concentrations and cultivation time on cellulase enzyme and bioethanol production by N. sitophila. The pretreatment of Napier grass was carried out using 1.5% (w/v) NaOH solution for 120 hours at 30 °C. After the pretreatment process, simultaneous saccharification and fermentation was conducted at 30 °C; pH 6.8-7.0 and agitation speed 130 Rpm with various of Napier grass substrate concentrations (10, 20 and 30 g l-1) and cultivation period within 24; 48; 72; 96 and 120 hours. The results show that the highest enzyme activity is 0.28 FPU/ml which was achieved at 120 hours of cultivation and 20 g/L substrate concentration of Napier grass. The highest ethanol content was obtained by 96 hours of simultaneous saccharification and fermentation (1.25 g l-1) using 20 g l-1 substrate concentration and the maximum ethanol yield is 0.30 g/g cellulose conducted at 30 g l-1 substrate concentration and 96 hours of fermentation.